2009
DOI: 10.1308/003588409x428261
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Rotator Cuff Tears and Repeated Subacromial Steroid Injections: A Case-Controlled Study

Abstract: INTRODUCTION Concern exists regarding potential damage to the rotator cuff from repeated corticosteroid injections into the subacromial space. PATIENTS AND METHODS In this retrospective, case-controlled study, 230 consecutive patients presenting to three orthopaedic units with subacromial impingement and investigated as an end-point with magnetic resonance imaging (MRI) of the shoulder were divided into groups having received less than three or three or more subacromial injections of corticosteroids. RESULTS W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
(21 reference statements)
0
32
0
1
Order By: Relevance
“…Many studies have reported the use of steroids for treating rotator cuff lesions . On the other hand, only a few studies have reported the use of HA to treat such lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported the use of steroids for treating rotator cuff lesions . On the other hand, only a few studies have reported the use of HA to treat such lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, physical rehabilitation has also been used. Although both steroid and hyaluronic acid (HA) injections have been commonly used as a conservative treatment for RCT, it remains unknown which method is more effective for pain relief Moreover, repeated steroid injections may result in local tissue degradation, including tendon tearing and steroid arthropathy …”
mentioning
confidence: 99%
“…Also, Bhatia et al16 reported that subacromial bursa injection of steroid in patients with subacromial impingement syndrome was not the cause of damage to rotator cuff because there was no statistically significant difference between 2 groups of 230 patients with clinical findings of subacromial impingement syndrome who were treated with triamcinolone >3 times and patients who were treated <3 times when comparing the 2 groups by determining whether there was of rotator cuff damage using MRI.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bhatia et al found that subacromial impingement should not be considered a causative factor in rotator cuff tears. Subacromial injections of corticosteroids were shown to be effective however in the improvement of rotator cuff tendonitis for up to a 9-month period post injection which probably makes it more effective than NSAID medication [35-37]. …”
Section: Conservative Managementmentioning
confidence: 99%